Determination of the threonine requirement for maintenance in Atlantic salmon (Salmo salar L.) fry with the diet dilution procedure - Abboudi, Tarik; Ooghe, W.; Larondelle, Yvan; Rollin, Xavier (Aquaculture Nutrition, 2007)
A study was conducted to evaluate the threonine (Thr) requirement for maintenance in Atlantic salmon using the diet dilution procedure (DDP). Fourteen groups of 60 salmon fry [1.46 g initial body weight (BW)] were fed on seven semi-purified diets containing graded levels of N (3-64 g kg(-1) dry matter) and L-Thr (1-39 g kg(-1) dry matter). Seven doses of Thr represented 1-31% of its ideal level for optimum protein deposition. Indispensable amino acids (AA) other than Thr were included in the same proportion as in the Atlantic salmon fry whole-body carcass. Protein deposition and Thr accretion were linear functions of Thr intake. At zero Thr intake fry lost 4.4 mg Thr kg BW-0.75 day) 1 and the Thr requirement for maintenance was 5.8 mg kg BW-0.75 day(-1), which represented 11% of the total need for Thr. Increasing doses of Thr did not show any effect on AA concentrations in whole-body protein, except for cystine. The linear relationship between Thr gain and Thr intake indicates a constant Thr cumulative efficiency (77%) at marginal Thr intake. Finally, our results suggest that (1) both the DDP and the graded supplementation technique can be used in Atlantic salmon fry for the determination of AA maintenance requirement and utilization efficiency, at least for Thr; (2) the dietary protein level has only a minor effect on the Thr maintenance requirement determination.